AgriTrack Digital Ordering Monitoring System for Ttangkkuet Green Farm. (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The AgriTrack Digital Ordering Monitoring System for Ttangkkuet Green Farm is designed to resolve the challenges faced by the farm owner in managing their business operations. The system focuses on improving the way orders are handled by providing features such as order management, receipt printing, order tracking, customer reviews, and product customization. This study follows the Agile Methodology, which allows the system to be built step by step, with regular feedback to make sure it meets the needs of the users. The system includes important features such as a responsive web-based platform, real-time product availability tracking, manual confirmation and notifications, OTP verification, and digital payment options. To better understand the problems faced by the farm owner—such as receiving orders and writing receipts by hand—the researchers conducted interviews, direct observations, and reviewed related studies. A purposive sampling method was used to choose the right people to take part in the study. A total of 9 participants were selected, including the farm owner, business partners, and customers. To measure how well the system is accepted and used, a Likert Scale survey will be given to the participants. After collecting the responses, statistical analysis will be done to check the usability and performance of the system. By solving the issues in the current process, the AgriTrack Digital Ordering Monitoring System aims to improve how reservations and orders are managed. This will help make operations smoother and increase customer satisfaction at Ttangkkuet Green Farm.